1993
DOI: 10.1136/thx.48.7.772
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal tuberculosis mimicking a tumour during treatment for nodal tuberculosis.

Abstract: A patient with cervical lymph node tuberculosis developed a tubercular ulcer in the oesophagus eight weeks after starting treatment. This was probably due to a drug related hypersensitivity reaction in an adjacent mediastinal lymph node and subsided with continued treatment. (Thorax 1993;48:772-773) Despite the frequent involvement of other mediastinal structures,' oesophageal tuberculosis is rare. We describe a patient with tuberculous ulceration of the oesophagus mimicking a mass lesion which appeared eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the second patient, the mediastinal lymph nodes enlarged while the patient was on antituberculous therapy and caused a fluctuating mass in the neck that ruptured and caused a discharging sinus in the neck through the mediastinoscopy wound. Enlargement of mediastinal lymph nodes while the patient is on antituberculous therapy has been reported recently by Kaur and colleagues 22 who described a case of cervical TB lymphadenopathy complicated by extrinsic esophageal compression and esophageal ulceration secondary to mediastinal lymph node enlargement that occurred while the patient was on antituberculous therapy. In addition, enlargement of superficial tuberculous lymph nodes has been well documented.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the second patient, the mediastinal lymph nodes enlarged while the patient was on antituberculous therapy and caused a fluctuating mass in the neck that ruptured and caused a discharging sinus in the neck through the mediastinoscopy wound. Enlargement of mediastinal lymph nodes while the patient is on antituberculous therapy has been reported recently by Kaur and colleagues 22 who described a case of cervical TB lymphadenopathy complicated by extrinsic esophageal compression and esophageal ulceration secondary to mediastinal lymph node enlargement that occurred while the patient was on antituberculous therapy. In addition, enlargement of superficial tuberculous lymph nodes has been well documented.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, enlargement of superficial tuberculous lymph nodes has been well documented. 2,22,23 Iles and Emerson 23 reported that 2 of 43 patients developed TB lymphadenopathy while they were on antituberculous therapy. This may have been due to hypersensitivity to tuberculin protein and to bacterial load.…”
Section: Discussionmentioning
confidence: 99%